Knowledge and health seeking behaviour of tuberculosis patients in Kerala, India - Paramasivam, Selvam; Thomas, Bina; Thayyil, Jayakrishnan; Rahim, Asma; Thavody, Jayakrishnan; M. P., Lilabi; V. K., Jayadev (International Journal Of Community Medicine And Public Health, 2016)
Background: Patients confront several problems in timely and effective utilization of TB health facilities which have often delayed diagnosis of TB. It is hence the need of the hour to look beyond the case detection rates towards other factors that can promote early diagnosis. Methods: A community-based cross-sectional study was conducted among newly diagnosed smear positive pulmonary tuberculosis patients aged ≥15 years on the Intensive Phase of treatment. A pretested semi-structured questionnaire was used to study knowledge, stigma, health seeking behaviour and other factors. Results: The predominant symptom for seeking care was cough (93.0%). 45.7% of patients sought the services of a health care provider within 2 weeks. Modern medicine was the preferred system for 94.7% of the patients. The majority (58.6%) of the patients consulted a private health facility. Illiterates and Below Poverty Line patients preferred government facilities. The average number of consultations before diagnosis was 3.11±1.9. 34.1% had adequate knowledge about tuberculosis and women had a significantly higher knowledge score. low per capita income, smoking and alcohol use, cough alone, cough with other symptoms, history of TB in Family, distance more than ≥ 5 km to health facility showed significant association with delayed health-seeking action (>14 days). Conclusions: Private practitioners and private hospitals were the predominant health providers preferred by the study subjects for the first consultation. Delayed health seeking action was probably due to the presence of a cough alone and coughs with other symptoms, history of tuberculosis among the family members and increased distance to TB health facility.